2019
DOI: 10.20961/agrotechresj.v3i1.25792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Type of Natural Substances Plant Growth Regulator on Nutmeg (<em>Myristica Fragrans</em>) Seedlings

Abstract: Nutmeg (<em>Myristica fragrans Houtt</em>) is an important spices in Indonesia. The advantages of nutmeg is essential oil content, the result of distillation which is for the spices industry, the manufacture of soaps, perfumes, cosmetics, have high economic value and are a source of foreign exchange to non oil &amp; gas, Indonesia is able to supply the needs of the market the world of up to 70% to 75%. Generally, nutmeg in Indonesia use generative propagation which has the strong root system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
0
7
0
6
Order By: Relevance
“…Each treatment was repeated 3 times so that there were 36 polybags. The results of this study showed that in observing the number of shoots the best-growing media treatment was T0 at the age of 6 WAP (4.33) and 7 WAP (4.56), the best concentration of onion extract was treatment B1 at 6 WAP (3,50) and 7 WAP (4,67), observing the number of roots with the best treatment B1 at the age of 8 WAP (3.00), observing the number of roots with the best B1 at the age of 8 DAP (3,96). There was no interaction between the growing media and onion extract.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Each treatment was repeated 3 times so that there were 36 polybags. The results of this study showed that in observing the number of shoots the best-growing media treatment was T0 at the age of 6 WAP (4.33) and 7 WAP (4.56), the best concentration of onion extract was treatment B1 at 6 WAP (3,50) and 7 WAP (4,67), observing the number of roots with the best treatment B1 at the age of 8 WAP (3.00), observing the number of roots with the best B1 at the age of 8 DAP (3,96). There was no interaction between the growing media and onion extract.…”
mentioning
confidence: 79%
“…It was further stated that if the cytokinin concentration was smaller than auxin, it would stimulate root growth, and if the cytokinin concentration was balanced with the auxin concentration, the shoot, leaf, and root growth would be balanced as well. According to Kurniati et al, 2019) that the onion extract contains high cytokinins close to the auxin content, namely 122.34 ppm and 140.11 ppm.…”
Section: Number Of Shootsmentioning
confidence: 99%
“…Tanaman sayuran yang ditanam di pekarangan rumah akan menghasilkan kualitas sayuran yang baik jika dilakukan pemeliharaan yang tepat salah satunya dengan diberi pupuk (Cokrowati & Diniarti, 2019;Herlina, L., K.K. Pukan, 2016;Kurniati et al, 2019;Rahmawati, 2021;Rahni, 2012). Pupuk yang disarankan adalah pupuk organik cair berfitohormon.…”
Section: Pendahuluanunclassified
“…Hal ini akibat efek dari zat yang terkandung dalam bawang merah terutama zpt alami, seperti auksin, sitokinin, dan giberelin. Menurut Kurniati et al (2019) 3.26 b 100 g L -1…”
Section: Hasil Dan Pembahasanunclassified